Peningkatan Pengendalian Internal Pada Pembelian Bahan Baku Di Masa Pandemi (PT. Gajah Mas Tulungagung) - Dwi Enggar Wati; Sri Dwi Estiningrum (Owner : Riset dan Jurnal Akuntansi, 2022)
Internal control has an important role for the company to minimize and expedite the company's operational activities. As the goal of a business organization is to generate the highest profit and guarantee the wealth of investors and creditors. The purpose of this study was to determine the improvement of internal control on the purchase of raw materials at PT. Gajah Mas Tulungagung during the pandemic. The results of this study indicate that the internal control in the process of purchasing raw materials in the pre-pandemic period by PT. Gajah Mas Tulungagung is by reconciling the inventory book with the stock of goods in the warehouse, internal control in the process of purchasing raw materials during the pandemic by PT. Gajah Mas Tulungagung, namely by separator of functional responsibilities and system of recording procedures, Constraints in implementing internal control in the process of purchasing raw materials during the pandemic by PT Gajah Mas Tulungagung is the Delay in Arrival of Ordered Goods due to long distances from suppliers, The company's efforts in internal control during the process of purchasing raw materials in During the pandemic period, companies are carried out by buying raw materials at low prices with the aim of minimizing expenses in the production process, and getting as much profit as possible from production.